2022
DOI: 10.1002/lio2.748
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of time‐restricted feeding on gentamicin cytotoxicity in mouse cochlea and vestibular organs

Abstract: Objective Time restricted feeding (TRF), which is an intermittent fasting protocol, has been reported to decrease the toxicity and mortality rate associated with systemic gentamicin (GM) administration. The aim of this study is to evaluate the effect of TRF on GM‐induced vestibular and auditory function in mice. Methods Japan Central Laboratory for Experimental Animals:Institute of Cancer Research (Jcl:ICR) mice were housed in a light–dark (LD) cycle (12:12) and were divided into three groups: (1) GM treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
(101 reference statements)
0
1
0
Order By: Relevance
“…It has been reported that the expression of brain-derived neurotrophic factor in the cochlea has a circadian rhythm and decreases its susceptibility to noise exposure. By entraining circadian clock genes and their downstream cascades, TRF is predicted to have a beneficial effect on the protection of the cochleovestibular system [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the expression of brain-derived neurotrophic factor in the cochlea has a circadian rhythm and decreases its susceptibility to noise exposure. By entraining circadian clock genes and their downstream cascades, TRF is predicted to have a beneficial effect on the protection of the cochleovestibular system [5,6].…”
Section: Introductionmentioning
confidence: 99%